2018
DOI: 10.1155/2018/4673814
|View full text |Cite
|
Sign up to set email alerts
|

Using IVIM-MRI and R2⁎ Mapping to Differentiate Early Stage Liver Fibrosis in a Rat Model of Radiation-Induced Liver Fibrosis

Abstract: Rationale and Objectives To investigate the utility of intravoxel incoherent motion MRI (IVIM-MRI) and R2⁎ mapping in diagnosing early stage liver fibrosis in a radiation-induced rat model. Materials and Methods Thirty rats were randomly divided into three groups with 10 rats in each group. Liver fibrosis was induced by exposure of right lobe of liver in each animal to 20 Gy of radiation. MRI examination was conducted at baseline, one month, two months, and three months after radiation using T1WI, T2WI, IVIM-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) is a noninvasive technique which was first proposed by Le Bihan et al ( 17 ) in 1986. It can sensitively reflect the tumor cellularity and microcirculation perfusion in tissues without the need of contrast agent ( 18 ), allowing for longitudinal monitoring of cellular and hemodynamic changes. We attempted to perform the IVIM-DWI to assess vascular normalization during anti-vascular treatment in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) is a noninvasive technique which was first proposed by Le Bihan et al ( 17 ) in 1986. It can sensitively reflect the tumor cellularity and microcirculation perfusion in tissues without the need of contrast agent ( 18 ), allowing for longitudinal monitoring of cellular and hemodynamic changes. We attempted to perform the IVIM-DWI to assess vascular normalization during anti-vascular treatment in the study.…”
Section: Introductionmentioning
confidence: 99%
“…33 In addition, prior research using a rat model of radiation-induced liver fibrosis showed that iron deposition, confirmed using Prussian blue staining, increased gradually from stage F0 to stage F2. 34 In viral hepatitis, however, no association was found between the amount of iron deposited and fibrosis in previous studies. 35,36 However, Son et al showed that liver volume tended to decrease gradually with the progression of liver fibrosis in patients with viral hepatitis, 37 which might decrease the density of parenchymal tissue or ROI and relatively increase susceptibility caused by intrahepatic iron deposits.…”
Section: Qsm Versus R2* In Liver Fibrosismentioning
confidence: 88%
“…Non-contrast enhanced relaxometric studies quantifying the longitudinal (T 1 ), transverse (T 2 *) and combined (T 1 ρ) magnetic relaxation time constants, which provide information on tissue microstructure and macromolecule content, have shown a good correlation of these parameters with liver fibrosis, without being specific for it [61][62][63][64]. (Supplementary file).…”
Section: Mrementioning
confidence: 99%